Submicron-grained Yb:Lu2O3 transparent ceramics with lasing quality - Yin, Danlei (2021)
We report on our recent progress of fabricating Yb3+-doped Lu2O3 transparent ceramics for 1 μm solid-state laser application. Well-dispersed 3.3 at.% Yb:Lu2O3 nanopowders were synthesized using a co-precipitation method. Without using any sintering aids, the Yb:Lu2O3 nanopowders could be densified by vacuum sintering at 1500°C/10 hours followed by HIPing at 1480°C/4 hours. Such obtained Yb:Lu2O3 ceramics had not only dense microstructure and submicron grain size of about 0.6 μm, but also in-line transmission of 80.0% at 600 nm. Preliminary continuous wave (CW) laser experiments with an uncoated Yb:Lu2O3 ceramic slab have demonstrated highly efficient CW laser oscillation at 1079.8 nm.